Layer-specific molecular signatures of colon anastomotic healing and leakage in mice - Hilal Sengul; Vasiliki Bantavi; Laura Gloeck; Andrew Y. F. Li Yim; Patrick Leven; Patrik Efferz; Bianca Schneiker; Mariola Lysson; Wouter J. De Jonge; Sven Wehner (Molecular Medicine)
Abstract Background Colon anastomotic leakage (CAL) is a postoperative complication originating from disturbed colon anastomotic healing (CAH). Wound healing involves several well-coordinated stages, which have not been comprehensively studied for CAH or CAL. This study aims to provide transcriptional profiles of different intestinal layers of anastomotic tissues throughout distinct healing stages and to identify CAL-related genes. Methods Proximal colon anastomosis was constructed with 8 interrupted sutures in mice. Six hours, 24 h and 72 h after surgery, anastomotic complications were assessed. Transcriptional profiles of inner (mucosa and submucosa) and outer (muscularis externa) layer of the anastomotic and naive control tissues were analyzed with 3’ bulk mRNA sequencing to identify the layer-specific healing and leakage pathways. Selective target genes differing between CAL and CAH were measured for their protein expression. Results Our data indicate that the mucosa/submucosa and muscularis externa enter inflammation stage at 6 h, proliferation stage at 24 h and tissue remodeling stage at 72 h during CAH. We observed that transcription profiles of the mucosa/submucosa, but not the muscularis externa, differ between CAH and CAL. Particularly, genes related to extracellular remodeling (including Col18a1 and Col16a1) and wound healing (Pdpn and Timp1) showed lower expression in the mucosa/submucosa of CAL tissue compared to CAH. Conformingly, protein levels for collagens as well IL-34 were decreased in CAL, while the TGF-β-pseudo-receptor BAMBI was increased in CAL compared to CAH tissues. Conclusions Mucosa/submucosa and muscularis externa are mostly in synchronization during the inflammation, proliferation, and extracellular remodeling stages during CAH. Transcriptional profiles within the anastomotic mucosa/submucosa differ between CAH and CAL in genes related to extracellular modelling and wound healing, indicating that genes of these pathways may contribute to CAL.